RESTSTENSI MASYARAKAT TERHADAP RENCANA PEMBANGUNAN PEMBANGKIT LISTRIK TENAGA SAMPAII DIGEDEBAGE BANDUNG - Muchtar Muchtar (Puslitbangkesos Kementerian Sosial RI, 2010)
This study is aimed to identifies the people's resistance to the planned construction of waste to energy (WTE) in Gedebage Bandung and other impacts forecast will appear. The type of study is exploratorf- qualitative. Informants: community and community leaders around lNTE construction plans, with data collection techniques: interviews, observations, and documentation. The study showed: (1) resistance (block-ing the activity of the project, conduct demonstrations) especially from the people closest to the location plan; (2) forecast the intpaci of (a) economic aspects, although the developer promised to consider local residents to be employed, but limited in the construction phase lNTE. Meanwhile, when lNTE has stood, only a few local residents who absorbed, so, increased the number of poor people; (b) health aspect, especially the people closest to the location plan, they worried with their health families, because the air pollution lNTE can cause frigidity not ollly hit the women but also men; (c) culture aspects, will occur behavioral changes at local Community because of meeting of various cultures. For that recommended: (1) the social aspects that have emerged, The Bandung City Gouernmeni must accommodate the views of communiiu's resistance with a democratic approach; (2) other aspects: (a) economic aspect, The Bandung City Gooernmeni tltrougli its policies to create jobs for local residents who are relatively less educated; (b) health aspects, Bandung City Government and developers need to explain fully the negative impact oflNTE air pollution scientifically by referring to experience of developed countries, and (c) cultural aspects, needs to prepare mentally conimunitu by involving social scientist in order to minimize the negative impacts due to the convergence of various different cultures.